Effects of brucea javanica seed extract on the number of embryos and ovarian structure in female ICR mice model. / Zatil Hidayah Marhadha - Marhadha, Zatil Hidayah (2015)
Brucea javanica is a plant species of the family Simaroubacea which is widely used as traditional medicine. Previous studies have reported that it is good at treating various ailments such as cancer, amoebic dysentery and inflammatory disease. However, so far there is yet any scientific evidence available on the potential effects of Brucea javanica on the female reproductive functions. Hence, the aim of this study is to investigate the effect of Brucea javanica seeds extract on the number of embryo production and ovarian histology. Twelve female ICR mice were randomly divided into four groups (three treatment groups and control group) with three members in each group. All groups were kept under similar conditions. Brucea javanica were prepared in 500, 800 and 1000mglkglday/doses and orally administered every day for twenty-one days. Distilled water was used for control group. At the end of treatment, the female mice were mated with male mice to get the copulation plug. Then, the female mice were killed after the plug was seen. Oviduct and ovary were collected for embryo retrieval and histological examination respectively. All mice in treatment groups showed not significantly reduced number of embryo produced. The ovarian histology also showed no obvious structural changes when compared to control group. However, treatment with Brucea javanica seems to reduce number of follicles but increased in the number of corpus luteum. In a conclusion, the results obtained from this study indicated that Brucea javanica seeds extract does give an effect on the female reproductive functions.